2009
DOI: 10.1359/jbmr.081212
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Dietary Patterns During Pregnancy and Childhood Bone Mass: A Longitudinal Study

Abstract: Maternal nutrition is a potentially important determinant of intrauterine skeletal development. Previous studies have examined the effects of individual nutrients, but the pattern of food consumption may be of greater relevance. We therefore examined the relationship between maternal dietary pattern during pregnancy and bone mass of the offspring at 9 yr of age. We studied 198 pregnant women 17-43 yr of age and their offspring at 9 yr of age. Dietary pattern was assessed using principal component analysis from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
84
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(86 citation statements)
references
References 20 publications
(30 reference statements)
2
84
0
Order By: Relevance
“…Nevertheless, these micronutrient imbalances are important, as borne out by the finding of global hypomethylation in rats with a vitamin B-12: folate ratio imbalance (38). In general, a balanced diet (and supplementation) is perhaps most likely to define a balanced fetal nutrient environment; for example, prudent diets (including more fruit, vegetables, and whole and unprocessed foods) in mothers have been shown to be associated with better bone mass accretion patterns in their offspring (39).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these micronutrient imbalances are important, as borne out by the finding of global hypomethylation in rats with a vitamin B-12: folate ratio imbalance (38). In general, a balanced diet (and supplementation) is perhaps most likely to define a balanced fetal nutrient environment; for example, prudent diets (including more fruit, vegetables, and whole and unprocessed foods) in mothers have been shown to be associated with better bone mass accretion patterns in their offspring (39).…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, maternal diet has been considered in terms of intake of specific nutrients, such as calcium and vitamin D. However, these nutrients comprise parts of broader dietary patterns and one recent study has explored maternal diet in more detail in relation to skeletal health in the offspring and showed that a high maternal prudent diet score (high intakes of fruit and vegetables, wholemeal bread, rice and pasta, yoghurt and breakfast cereals and low intakes of chips and roast potatoes, sugar, white bread, processed meat, crisps, tinned vegetables and soft drinks) was found to be associated with greater bone size and areal BMD in the offspring [22]. The observed effect was independent of social class, education, maternal height, maternal smoking status and late pregnancy vitamin D levels as well as childhood height, weight and exercise.…”
Section: Bone Density Geometry and Strengthmentioning
confidence: 99%
“…In some studies, similar patterns were found with different names, such as "vegetable" [1] "health conscious" [24] and "prudent" [25,26].…”
Section: Discussionmentioning
confidence: 53%
“…This may also lead to decreased risk of childhood obesity, respiratory diseases, high blood pressure, dyslipidemia, and other health problems [3,25].…”
Section: Discussionmentioning
confidence: 99%